Analysis of National Institutes of Health Funding in Hand Surgery - Silvestre, Jason (Hand (N Y), 2018)
Background: Federal research dollars help investigators develop biomedical therapies for human diseases. Currently, the state of funding in hand surgery is poorly understood. This study defines the portfolio of National Institutes of Health (NIH) grants awarded in hand surgery. Methods: This was a cross-sectional study of hand surgeons in the US. Faculty members of accredited hand surgery fellowships and/or members of the American Society for Surgery of the Hand were queried in the NIH RePORT database for awards obtained during 2005-2015. Results: Of 2317 hand surgeons queried, only 18 obtained an NIH grant (0.8%). Thirty-eight unique grants were identified totaling $42 197 375. R01 awards comprised the majority of funding (78.0%) while K08 awards accounted for 1.1%. The K-to-R transition rate was zero. The National Institute of Arthritis and Musculoskeletal and Skin Disease supported the most funding (65.2%), followed by the National Institute of Neurological Disorders and Stroke (30.8%). There was no statistically significant difference in NIH funding totals with hand surgeon characteristics. Funding supported translational (46.0%), basic science (29.6%), clinical (21.0%), and education-based (3.4%) research. Peripheral nerve (33.3%) and bone and joint disease (30.1%) received the most research funding. Conclusions: Less than 1% of hand surgeons obtain NIH research grants. Of the 2 identified K08 awards, none led to a subsequent R award. Future research should identify barriers to grant procurement to design effective policies to increase NIH funding in hand surgery.